Subacute thyroiditis post-Pfizer-BioNTech mRNA vaccination for COVID-19. (15th December 2021) - Khan, Farooq; Brassill, Mary Jane
Abstract : Summary: There is emerging evidence of an association between COVID-19 vaccination and subacute thyroiditis. We present the case of a 42-year-old female healthcare worker who was diagnosed with subacute thyroiditis 4 days after receiving her second dose of Pfizer-BioNTech vaccine. Her clinical course followed the classical pattern for thyroiditis with spontaneous return to euthyroidism at 6 months post-presentation. The autoimmune/inflammatory syndrome induced by adjuvants has been implicated as a cause of autoimmune conditions post-vaccination and is a potential mechanism for subacute thyroiditis in our case. Learning points: Subacute thyroiditis should be considered in all patients who receive any kind of vaccine for COVID-19 and subsequently develop symptoms or signs of hyperthyroidism or neck pain. Subacute thyroiditis is a self-limiting condition, and recognising it is important as no specific thyroid treatment (antithyroid drugs or thyroid hormone replacement) is necessary for most patients. The autoimmune/inflammatory syndrome induced by adjuvants may be an under-recognised cause of endocrinopathies and should particularly be considered post-vaccination.